163 Amoxicillin Allergy in Children… Common or Uncommon? (#151 with changes). (11th October 2021) - Silva, Íris Santos; Francisco, Catarina Macedo; Ribeiro, Joana Filipe; Virtuoso, João; Guerra, Pedro; Oliveira, Rita S
Abstract : β-Lactam antibiotics are safe and cost-effective antibiotics, being amoxicillin the most common antibiotic used among the paediatric population. Many patients report allergic reactions to this antibiotic, but amoxicillin allergy range between 1-10%. However, clinicians hesitate to prescribe it when a suspected, but unproven, allergy exists. Our aim is to confirm amoxicillin allergy in children with clinical suspicion. This study was done between January 2018 and December 2020, in children younger than 18 years, admitted to the emergency room with suspicion of clinical allergic reaction to amoxicillin. According to the protocol of our hospital, they were referred for pediatric allergology appointment to perform prick tests and afterwards oral provocation test. A total of 57 cases were referred for evaluation. The average age was 8.4 (1-17) years old, and 53% were female. The suspicion was based on late rash reaction presented in 68, .4%, urticarial exanthema in 19.3%, edema in 8.8%, vomit in 8.8%, cutaneous rash in 7% and dyspnea in 2, 1%. In 18 patients, specific IgE screening for amoxicillin was performed, but all results were negative. All children did a prick test for amoxicillin and oral provocation test. There were no positive results for prick tests, but two positive results in the oral provocation test (3.5%). Confirmation of amoxicillin allergy, before deciding to use it is or not, is an important tool for antimicrobial stewardship and, consequently, to decrease the rate of antibiotic resistance. So far, in our hospital, there were only two positive results.